2020
DOI: 10.1088/1757-899x/823/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Plant extract-assisted biosynthesis of zinc oxide nanoparticles and their antibacterial application

Abstract: ZnO nanoparticles are multi-purposes materials that can be synthesized by several methods, including physical and chemical routes. A novel synthesis method of ZnO nanoparticles is the biological method using plant extracts as reducing and capping agents, such as the fruit extract of Averrhoa bilimbi. Plant extracts are superior agents for synthesizing nanoparticles because it provides essential phytochemical substances as reductor, capping agents, and free from toxicants. In this study, the effects of precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
8
1
Order By: Relevance
“…Rahayu et al synthesized ZnO nanoparticles by using fruit extract of Averrhoa bilimbi as reducing and capping agents. They observed that during the synthesis process at 70 °C 47 . The formation of deep white precipitate and faster evaporation of solvent has occurred.…”
Section: Resultsmentioning
confidence: 99%
“…Rahayu et al synthesized ZnO nanoparticles by using fruit extract of Averrhoa bilimbi as reducing and capping agents. They observed that during the synthesis process at 70 °C 47 . The formation of deep white precipitate and faster evaporation of solvent has occurred.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectra of the biosynthesized nanoparticles were recorded by scanning the particles in the range 400-4000 cm -1 using Thermo Nicolet, Avatar 370' FTIR spectrometer by KBr disc method. The crystalline morphology and phase structure of the synthesised nanoparticles were determined by X-ray diffractometer with high intensity CuKα radiation over the 2θ range of 20-80 °.The average crystallite size was calculated using Scherrer equation [27].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…There are many methods to prepare zinc nanoparticles. Physical methods, for example, include melt mixing, laser ablation, electric deposition, ball milling, physical vapour deposition, sputter deposition, and ion implantation (Rahayu et al, 2020). While Sol-gel, chemical-mechanical synthesis, microwave method, thermal evaporation, hydrothermal technique, vapor transport synthesis, and precipitation method are some chemical methods used to make nano-zinc oxide (Sabir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The precursor concentration of zinc nitrate has a significant impact on the production of nano-ZnO when Aloe vera extract is employed according to (Rasli et al, 2020). These compounds include enzymes, proteins, flavonoids, phenols, alkaloids, tannins, soaps, and others, which play a key role in the reduction process of particles (Lakshmeesha et al, 2019 andRahayu et al, 2020). In addition, using zinc acetate compound as a starting material and adding Ixora coccinea leaf extract, (Yedurkar et al, 2016) were able to generate spherical zinc oxide nanoparticles with a high degree of stability.…”
Section: Introductionmentioning
confidence: 99%